2011
DOI: 10.1002/mabi.201000395
|View full text |Cite
|
Sign up to set email alerts
|

BSA Adsorption on Differently Charged Polystyrene Nanoparticles using Isothermal Titration Calorimetry and the Influence on Cellular Uptake

Abstract: BSA adsorption onto negatively and positively charged polystyrene nanoparticles was investigated. The nanoparticles were characterized in terms of particle size, zeta potential, surface group density, and morphology. The adsorption behavior of BSA on the particle surface, as a function of pH and overall charge of the particle, was studied using ITC. Different thermodynamic data such as enthalpy changes upon binding and stoichiometry of the systems were determined and discussed. The degree of surface coverage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
129
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 31 publications
(42 reference statements)
13
129
1
2
Order By: Relevance
“…[13][14][15] Furthermore, it has been previously suggested that the formation of a protein corona around nanoparticles might reduce membrane adsorption, 10,16 and that interaction with the membrane may be important in permitting cellular entry. 12,17 Therefore, the potential for serum-dependent cellular interactions of a well-characterized type of nanoparticle (20 nm carboxylate-modified polystyrene beads), which are commercially available with a variety of fluorescent tags, was evaluated. HeLa human carcinoma cells were incubated with nanoparticles in the presence or absence of serum.…”
Section: Serum Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Furthermore, it has been previously suggested that the formation of a protein corona around nanoparticles might reduce membrane adsorption, 10,16 and that interaction with the membrane may be important in permitting cellular entry. 12,17 Therefore, the potential for serum-dependent cellular interactions of a well-characterized type of nanoparticle (20 nm carboxylate-modified polystyrene beads), which are commercially available with a variety of fluorescent tags, was evaluated. HeLa human carcinoma cells were incubated with nanoparticles in the presence or absence of serum.…”
Section: Serum Effectsmentioning
confidence: 99%
“…4 It has been determined that carboxylate modification of polystyrene nanoparticles can promote interactions with proteins, 11 and reduced cell surface binding was observed for larger polystyrene particles (eg, ∼200 nm) incubated in the presence of serum. 12 Therefore, studies were performed to assess potential serum-dependent effects on nanoparticle interactions with cells, and potential mechanisms for nanoparticle internalization. Taken together, the results demonstrate a striking serum dependence for plasma membrane binding and subsequent nanoparticle entry into cells via clathrin-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrene particles, PLGA particles, polysaccharide NPs, and iron oxide NPs acted less cytotoxically on nonphagocytic cells in the presence of serum. 3,9,105,106 Particularly, serum reduces the effects on membrane integrity. Potential causes for the mitigating effect of protein include instability of the suspension in the presence of proteins and masking of the reactive surface of the NPs, avoiding the interaction of the NPs with the plasma membrane and the generation of ROS.…”
Section: Serum Effectsmentioning
confidence: 99%
“…The decreased cytotoxicity in the presence of serum was usually correlated with a lower cellular uptake. 105 In phagocytic cells, where increased cytotoxicity in the presence of serum was reported, 107 serum coating is known to increase the cellular uptake of particles.…”
Section: Serum Effectsmentioning
confidence: 99%
“…The molecule is flexible and amorphous, consisted of amino acids and peptide bonds (Nakanishi et al, 2001;Rogalinski et al, 2005) and has an isoelectric point of approximately pH4.7 (Chiku et al, 2008). There is a consensus that surface properties of BSA vary across the molecule giving rise to charge heterogeneity (Baier et al, 2011), along with hydrophobic and hydrophilic regions (Yoon et al, 1998). Consequently, morphological models of BSA needs simplification to certain degrees: it is described either as a globular ellipsoid of about 14 x 3.8 x 3.8 nm (Ke et al, 2009;Togashi et al, 2009), a heart-shaped solid with three different domains (Voros, 2004), or a flexible foldable polymer (Chiku et al, 2008).…”
Section: Double Pulse Column Experiments (Dpes)mentioning
confidence: 99%